Discussing HPV with oropharyngeal cancer patients: A cross-sectional survey of attitudes in health professionals - Dodd, Rachael H. (Oral Oncol, 2017)
BACKGROUND: Human papillomavirus (HPV) is now known to cause a significant proportion of head and neck cancers (HNC). Qualitative research has shown that some health professionals find it difficult to discuss HPV with patients due to its sexually transmitted nature, and have concerns about their own knowledge of the virus. We used a survey to quantify attitudes towards discussing HPV among HNC health professionals. METHODS: We carried out a cross-sectional survey of HNC health professionals (n = 260) in the UK and Ireland, assessing participants’ knowledge of HPV, their experiences of and attitudes towards discussing HPV with patients, and their willingness to discuss HPV with their patients in the future. RESULTS: Overall, health professionals had good knowledge of HPV (mean score: 9.97 out of 12). Oncologists had significantly greater knowledge than specialist nurses, speech and language therapists and ‘other’ health professionals. Most were willing to discuss HPV with patients (mean = 4.3 out of 5). Willingness to discuss HPV in the future was associated with higher HPV knowledge (r = 0.35, p < 0.001), fewer negative and more positive attitudes towards discussing HPV (r = −0.23 and r = 0.20 respectively, both p < 0.001), fewer personal barriers (r = −0.49, p < 0.001) and greater confidence (r = 0.58, p < 0.001). CONCLUSION: Knowledge, experiences and attitudes to discussing HPV varied across HNC health professionals. Addressing gaps in health professionals’ HPV knowledge and improving their confidence in discussing HPV with patients may increase their willingness to have such conversations. This may help minimise the negative psychosocial consequences of an HPV diagnosis in this patient group.